Development of Blush On Powder Formulation using Beetroot Extract (Beta vulgaris L.) as Natural Colorant: Pengembangan Formulasi Blush On Powder menggunakan Ekstrak Umbi Bit (Beta vulgaris L.) sebagai Pewarna Alami - Feronika Evma Rahayu; Evi Sri Maulidi Risalah; Aluwi Nirwanasari; Ing Mayfa Situmorang; Feri Setiadi (Universitas Airlangga, 2025)
Research on the development of natural dyes using beetroot (Beta vulgaris L.) has been investigated. Beetroot extract was obtained using the maceration method and then characterized through phytochemical screening tests, TLC (Thin Layer Chromatography), FT-IR (Fourier Transform Infrared), and XRD (X-ray Diffraction). The extract was developed as an active ingredient in a blush on powder formulation. The formulation was evaluated through organoleptic testing, homogeneity, pH, and spreadability tests, as well as stability testing using the freeze and thaw method. The results showed that the beetroot extract yield was 4.64%, containing secondary metabolites in the form of alkaloids, flavonoids, saponins, tannins, and terpenoids, with an Rf value of 0.54, the presence of chemical structures in the form of O-H, C-H, C-H, and R-CH=CH-R, and an amorphous form. Formulation was carried out by varying the beetroot extract to F1 (2%), F2 (5%), and F3 (8%) and control F0. Based on organoleptic testing, the formulations showed light brown color for F1, brown for F2, and dark brown for F3, homogeneous, pH in the range of 6.56-6.94, and spreading power in the range of 5-7 cm. The stability test showed a normality test >0.05, indicating that the formulation was normally distributed. The homogeneity test >0.05 showed no significant differences between the formulations. The one-way ANOVA test p<0.05 showed that the formulation had an effect on the pH value, while the post hoc Tukey HSD test p<0.05 showed no significant differences between the formulations. Keywords: Beetroot, TLC, FT-IR, XRD, Blush On, Natural Colorant